Indoor air pollution from solid fuels and hypertension: A systematic review and meta-analysis. (April 2020) - Li, Lanyu; Yang, Aiming; He, Xiaotao; Liu, Jiangtao; Ma, Yueling; Niu, Jingping; Luo, Bin
Abstract: Cardiovascular diseases (CVD) are leading global health issue. More studies have linked indoor air pollution from solid fuel usage to hypertension risk, a leading risk factor for CVD. We conducted a systematic review and meta-analysis of observational studies assessing the relationship of indoor air pollution from solid fuel with hypertension risk. Using a protocol standardized a priori, two independent reviewers searched PubMed, the Cochrane Library, Ovid MEDLINE, Web of Science and EMBASE for available studies published before Dec.1, 2019. A random effects model was used to analyse the pooled results. Out of 3740 articles, 47 were reviewed in depth and 11 contributing to this meta-analysis. The use of household solid fuel was significantly associated with an increased risk of hypertension (OR = 1.52, 95% CI = 1.26 to 1.85). The smoking-controlled group (OR = 2.38, 95% CI = 1.58 to 3.60) had greater effect size of hypertension than the uncontrolled group (OR = 1.11, 95% CI = 1.10 to 1.11). These findings implicate that indoor air pollution from solid fuel may be an important risk factor for hypertension. Graphical abstract: Image 1 Highlights: The association between indoor air pollution from solid fuel usage and risk of hypertension was systemically reviewed. Indoor air pollution from solid fuel is an important risk factor for hypertension.